Macroeconomic and financial stability challenges for acceding and candidate countries - Adalbert Winkler; Roland Beck (European Central Bank (ECB), 2006)
This paper – based on a report by a Task Force established by the International Relations Committee (IRC) of the European System of Central Banks (ESCB) – reviews macroeconomic and financial stability challenges for acceding (Bulgaria and Romania) and candidate countries (Croatia and Turkey). In an environment characterised by strong growth and capital inflows, the main macroeconomic challenges relate to the recent pick-up of inflation and the large and widening current account deficits. Moreover, rapid credit growth has been a recent feature of financial development in all countries and thus constitutes the main financial stability challenge. In general, monetary authorities have responded to these challenges by tightening monetary conditions and prudential standards, with concrete measures also reflecting the different monetary and exchange rate regimes in the region. The paper also highlights four specific features of financial development in the countries under review, namely the dominance of banks in financial intermediation, the strong participation of foreign-owned banks, the widespread use of foreign currencies and the strengthening of supervisory frameworks.
Keywords: E65; G21; G38; O16; P27; 330; South-East Europe; macroeconomic performance; credit growth; financial stability.; Kreditmarkt; Finanzsystem; Geldpolitik; Bulgarien; Rumänien; Kroatien; Türkei; Wirkungsanalyse